Effective utilization of harvested water: Natural resource management initiatives under Farmer FIRST Programme - Nirmala, G.; Narsimlu, B.; Reddy, B. Sanjeeva; Dinesh, A.; P. K., Pankaj; Reddy, A. Gopala Krishna; C. N., Anshida Beevi; Singh, V. K.; Reddy, A. R.; Burman, Rajarshi Roy (Indian Farming, 2025)
Efficient management of water resources is critical for sustainable agriculture, especially in semi-arid and rainfed regions. Under the Farmer FIRST Programme, several interventions were implemented to enhance water harvesting and its optimal utilization. These interventions included construction of farm ponds, installation of drip irrigation systems and rain guns, renovation of existing check dams, and demonstration of conservation furrows. This article highlights the effectiveness of these interventions in improving water availability, enhancing crop productivity, and reducing input costs for farmers.